SAVI Learning Model in Improving Students' Learning Interest and Thinking Ability in Balaghah Learning - Ulin Nuha, Muhammad Afthon; Nisa, Ida Fauziatun; Anwar, Saeful; Musyafaah, Nurul (Jurnal Internasional Pendidikan Bahasa Arab, 2023)
This study aims to determine the effect of the SAVI learning model (Somatic, Auditory, Visualization, Intellectual) on students' learning interests and critical thinking skills in the Balaghah subject at the Adnan Al-Charis Bojonegoro Islamic Boarding School. This study used a quantitative approach with a quasi-experimental research type with a non-equivalent control group design. Class A is the control class with 15 students, and class B is the experimental class with 15 students. Data collection methods include observation, questionnaires, tests, and documentation. Meanwhile, data analysis used descriptive statistics, sample t-test, and the N-Gain test. From the results of this study, it was obtained 1) The SAVI learning model was effective in increasing students' interest in learning. The results of the independent sample t-test (2-tailed) < 0.05, which is 0.000; 2) The SAVI learning model is less effective in improving students' critical thinking skills. The N-Gain result for the experimental class is 59%; 3) There is an influence between the SAVI learning model on students' learning interest, the results of Sig (2-tailed) < 0.05, which is equal to 0.000, while the SAVI learning model has no influence on students' critical thinking skills, the results of Sig (2-tailed) > 0.05, namely of 0.903.